Perormance evaluation tests (1997)
The following examples of tests were descripted: 10 stride test for 100m and 200m athletes 150m Endurance test for 100m athletes 250m Endurance test for 200m athletes 30 metre acceleration test for 100m and 200m athletes 60 metre speed test for 100m and 200m athletes 400m Control tests Balke VO2 max test Cooper VO2 max test Flying 30m speed test for 100m and 200m athletes Kosmin test - 800m & 1500m time predictor Leg Elastic Strength tests Multistage Fitness Test or Beep Test - VO2 max test Quadrathon an excellent all round test. RAST - Running-based Anaerobic Sprint Test 400m Drop off - Anaerobic test for 100m and 200m athletes Strength Endurance tests Wingate Anaerobic 30 cycle Test - Cycling based Anaerobic Test